Association of Gestational Diabetes with Parental Diabetic Mellitus and Impaired Glucose Tolerance: A Cross-Sectional Study - Kamran Baig Memon, Danish Kumar, Tazeem Hussain, Syeda Iqra Mushir, Zafarullah Phull, Suresh Kumar, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the association of gestational diabetes with parental diabetic mellitus and impaired glucose tolerance Study design: A cross-sectional study Place and Duration: This study was conducted at Jahra Hospital Kuwait from February 2021 to February 2022 Methodology: This study includes 100 women with gestational diabetes. They were aged 35 (±5) years. They were tested by fasting plasma glucose (fpg). There were 61 women who either had diabetes or fasting hyperglycemia (fpg = >5.4 millimole/l). A total of 35 women had their parents alive. Of these 35 women’s parents, 14 women’s parents agreed to test their metabolism. Their metabolism was tested by CIGMA (continuous infusion of glucose with model assessment). Results: Among those 14 families, 7 probands had diabetes and the other 7 had impaired glucose tolerance (IGT). The women were aged 36 (±4) years with a BMI of 27 (±5) kilograms/m2. The parents were aged 63 (±5) with a BMI of 30 (±5) kilograms/m2. The presence of glucose intolerance defined their affection status (an age and obese matched population with fpg or post-infusion attained plasma glucose levels greater than 3 standard deviation). Among those 14 families, 5 probands did not have any parent affected, which represents 35.7%, 3 probands had both parents affected, which represents 21.4%, and 6 probands had only 1 parent affect, which represents 42.9%. Only 3 of proband’s parents were affected by diabetes as explained by WHO criteria. Practical implication This paper outlines some of the growing evidence showing pregnant women with gestational diabetes mellitus are more likely to give birth to diabetic mothers. These preliminary findings' are provocative implications to encourage additional research. Conclusion: In conclusion, examining women with gestational diabetes, who have both parents available for this research, helps to find probands with IGT or diabetes. Those who had neither parents impacted with diabetes nor IGT were representing a significant portion which was much the same as elementary families of NIDDM. Keywords: diabetes mellitus, gestational diabetes, parents, impaired glucose tolerance